UMUR SIMPAN DAN KESUKAAN PERMEN JELLY EKSTRAK DAGING DAN KULIT BUAH NAGA - Diva, Aisha Diva Medina; Elida; Yuliana; Mustika, Sari (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
This study aims to analyze the differences in shelf life and acceptability of jelly candies made from red dragon fruit flesh extract and red dragon fruit peel extract. The research employed a quantitative approach with a Completely Randomized Design (CRD). The shelf-life test was carried out for 72 days with five untrained panelists by observing mold growth, taste changes, aroma changes, and color changes. The data were analyzed using Analysis of Variance (ANOVA) and followed by the Duncan Multiple Range Test (DMRT) to determine significant differences between treatments. The acceptability test was conducted with 50 untrained panelists using the hedonic test, assessing color, aroma, texture, and taste attributes. The results were analyzed using the t-test to identify differences in panelists’ preference levels. The results showed that mold growth occurred faster in jelly candies made from red dragon fruit flesh extract, while taste and color changes appeared earlier in those made from peel extract. Aroma changes in both treatments occurred at the same time. The ANOVA results indicated significant differences in several shelf-life parameters, while the t-test results revealed significant differences in all acceptability aspects. The mean scores for color (6.43), aroma (6.33), texture (6.17), and taste (6.21) in jelly candies made from red dragon fruit flesh extract were higher than those made from peel extract—color (5.72), aroma (5.91), texture (5.78), and taste (5.77). It can be concluded that jelly candies made from red dragon fruit flesh extract have a relatively shorter shelf life but are more preferred by panelists compared to those made from peel extract. Keywords: shelf life, acceptability, jelly candy, dragon fruit